Age-Related Electrocardiographic Characteristics of Male Junior Soccer Athletes - Cavarretta, Elena; Sciarra, Luigi; Biondi-Zoccai, Giuseppe; Maffessanti, Francesco; Nigro, Antonia; Sperandii, Fabio; Guerra, Emanuele; Quaranta, Federico; Fossati, Chiara; Peruzzi, Mariangela; Pingitore, Annachiara; Stasinopoulos, Dimitrios M.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Very limited data exist on normal age-related ECG variations in adolescents and no data have been published regarding the ECG anomalies induced by intensive training, which are relevant in pre-participation screening for sudden cardiac death prevention in the adolescent athletic population. The purpose of this study was to establish normal age-related electrocardiographic measurements (P wave duration, PR interval, QRS duration, QT, and QTc interval) grouped according to 2-year age intervals. Methods A total of 2,151 consecutive healthy adolescent Soccer athletes (trained for a mean of 7.2 ± 1.1 h per week, 100% male Caucasians, mean age 12.4 ± 1.4 years, range 7–18) underwent pre-participation screening, which included ECG and transthoracic echocardiography in a single referral center. Results Their heart rate progressively slowed as age increased (p < 0.001, ranging from 80.8 ± 13.2 to 59.5 ± 10.2 bpm), as expected. The P wave, PR interval, and QRS duration significantly increased in older age classes (p = 0.019, p = 0.001, and p < 0.001, respectively), and after Bonferroni's correction, the difference remained significant in all age classes for QRS duration. The QTc interval diminished progressively with increasing age (p = 0.003) while the QT interval increased progressively (p < 0.001). Conclusions Significant variations in the normal ECG characteristics of young athletes exist between different age groups related to increasing age and training burden, thus, age-specific reference values could be adopted, as already done for echocardiographic measurements, and may help to further discriminate potentially pathologic conditions.